Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jsfa.11777
|View full text |Cite
|
Sign up to set email alerts
|

Theabrownin isolated from Pu‐erh tea regulates Bacteroidetes to improve metabolic syndrome of rats induced by high‐fat, high‐sugar and high‐salt diet

Abstract: BACKGROUND Theabrownin (TB), a high macromolecular compound and a characteristic component of Pu‐erh tea, is able to markedly regulate blood lipid and glucose metabolism. We hypothesized that TB could ameliorate metabolic syndrome induced by high‐fat, high‐sugar and high‐salt diet (HFSSD). RESULTS To test these hypotheses, we fed rats with HFSSD and administered a gavage of TB. HFSSD successfully induced metabolic syndrome in rats. TB significantly improved serum lipid status, prevented obesity and fasting blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Theabrownin may reduce intracellular lipid synthesis and accumulation by promoting the levels of adenosine triphosphate-binding transporter A1 and cholesterol 7α-hydroxylase in HepG2 cells [30][31] . Gavage of theabrownin in the high glucose model rats significantly reduced the extent of liver and pancreatic lesions and improved insulin resistance [32] . And recently, theabrownin was shown to be the main active component of Pu-erh tea in lowering cholesterol [18] , which balanced liver lipid homeostasis in mice by regulating gut microbes as well as bile acid metabolism.…”
Section: Discussionmentioning
confidence: 90%
“…Theabrownin may reduce intracellular lipid synthesis and accumulation by promoting the levels of adenosine triphosphate-binding transporter A1 and cholesterol 7α-hydroxylase in HepG2 cells [30][31] . Gavage of theabrownin in the high glucose model rats significantly reduced the extent of liver and pancreatic lesions and improved insulin resistance [32] . And recently, theabrownin was shown to be the main active component of Pu-erh tea in lowering cholesterol [18] , which balanced liver lipid homeostasis in mice by regulating gut microbes as well as bile acid metabolism.…”
Section: Discussionmentioning
confidence: 90%
“…After supplementation with CKT, the composition and structure of the gut microbiota changed, and the changes were reflected in the increase in Bacteroidota and the decrease in Firmicutes . Bacteroidota and Firmicutes are the main components of the gut microbiota, accounting for more than 90% of the gut microbiome in humans and mice (Stojanov et al., 2020; Yue et al., 2022). The Firmicutes/Bacteroidetes (F/B) ratio is widely accepted to have an important influence in maintaining normal intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the serum levels of adiponectin, leptin, and glucokinase are elevated after the TB intervention. 14,15,18 TB reduces hepatic triglyceride and cholesterol levels to greatly reduce fat deposition and prevent the formation of fatty liver. 16 TB also influences the activity of fatty acid oxidation-related enzymes in hepatocytes, increasing the activity of hormone-sensitive lipase (HSL) and carnitine palmitoyltransferases I and II (CPT I and CPT II), as well as inhibiting 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA).…”
Section: Discussionmentioning
confidence: 99%
“…17 TB from Pu-erh tea also affects inflammation-related gut microbiota, such as reducing the increase in the ratio of Firmicutes / Bacteroidetes induced by a HFD. 18 Wang et al found that TB from Fu Brick tea increased the content of short chain fatty acids, especially butyrate, activating AMP activated protein kinase-peroxisome proliferator activated receptors-γ Co activating factor-1 α (AMPK-PGC1 α). The signaling pathway enhanced fat browning and upregulated the expression of heat producing genes uncoupling protein 1 (UCP-1) and PR domain protein 16 (PRDM16) closely related to lipolysis in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%